The Importance of Social Capital for Faith-Based Organizations in the New Normal Adaptation of West Sumatera - Inda Mustika Permata; Bima Jon Nanda; Rifki Dermawan (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
AbstractThis paper seeks to explain the importance of faith-based organizations as social capital during the new normal era in West Sumatra. Considering West Sumatra is identical with the strong Islamic Identity and the increase of Covid-19 cases which put the region in the 6th highest number in Indonesia, this research is imperative to be conducted. Referring to WHO’s policy, the local government of West Sumatra has imposed several regulations for new normal adaption and controlling the Covid-19 in the society. Therefore, this paper uses qualitative methods and social capital is applied for interpreting data. The data used in this study is the primary and secondary data—the primary data. We argues that the religious character of West Sumatra society provides opportunities for faith-based organizations to support the government in reducing the number of positive cases by educating people through Ulama who actively play a role in daily life. Abstrak Tulisan ini berupaya untuk menjelaskan mengenai pentingnya organisasi berbasis agama sebagai modal sosial pada masa new normal di Sumatera Barat. Sumatera Barat identik dengan identitas Islam yang kuat. Peningkatan kasus Covid-19 menempatkan Sumatera Barat pada urutan ke-6 di Indonesia. Maka dari itu penelitian ini menjadi penting untuk dilakukan. Mengacu pada kebijakan WHO, Pemerintah Daerah Sumatera Barat telah memberlakukan peraturan tentang adaptasi new normal dan pengendalian Covid-19 di masyarakat. Tulisan ini menggunakan metode kualitatif dan modal sosial digunakan untuk menginterpretasikan data. Jenis data primer dan data sekunder digunakan dalam tulisan ini. Kami berpendapat bahwa karakter masyarakat Sumatera Barat yang agamais memberikan peluang bagi organisasi berbasis agama dalam mendukung pemerintah menekan jumlah kasus positif dengan mendidik masyarakat lewat ulama yang aktif berperan dalam kehidupan sehari-hari.